Deposition of novel bioactive nanoflower-like sodium titanate on TiO2 coating via anodic oxidation for biomedical applications - Lee, T.C.; Abdullah, H.Z.; Koshy, P.; Idris, M.I. (ScienceDirect, 2018)
Bioactive coatings were prepared on titanium foils using anodic oxidation at applied voltage of 350 V and current density of 70 mAcm2 for 10 min. New formulation of electrolyte was introduced which consist of 0.04 M b-glycerophosphate (b-GP), 0.4 M calcium acetate (CA), and 1.0 M sodium hydroxide (NaOH) with different volume fractions. The results showed that the nanoflower sodium titanate was deposited on the titanium which anodically oxidised in electrolyte containing 50 vol% of b-GP + CA and 50 vol% NaOH. After soaking in SBF for 7 days, highly crystalline bone-like apatite was fully covered on surface of that particular sample.